2021
DOI: 10.3390/medicina57020158
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcome of Infective Endocarditis in a University Hospital in Romania

Abstract: Background and Objectives: Characterization of patients with endocarditis regarding demographic, clinical, biological and imagistic data, blood culture results and possible correlation between different etiologic factors and host status characteristics. Material and methods: This is a retrospective observational descriptive study conducted on patients older than 18 years admitted in the past 10 years, in the Cardiology Clinic of the Clinical County Emergency Hospital Oradea Romania, with clinical suspicion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1
10

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 37 publications
2
15
1
10
Order By: Relevance
“…On the other hand, Vitamin D is connected to numerous CVDs, including infectious myocarditis, which is caused by aberrant immunological reactions as a result of vitamin D receptor inadequacy. 38,39 In the current study, we found that people with prediabetes have greater CVR scores than normal participants regardless of their (25(OH)D) levels, we also did not identify a significant link between HbA1c and (25(OH)D) levels in prediabetics or healthy participants.…”
contrasting
confidence: 66%
“…On the other hand, Vitamin D is connected to numerous CVDs, including infectious myocarditis, which is caused by aberrant immunological reactions as a result of vitamin D receptor inadequacy. 38,39 In the current study, we found that people with prediabetes have greater CVR scores than normal participants regardless of their (25(OH)D) levels, we also did not identify a significant link between HbA1c and (25(OH)D) levels in prediabetics or healthy participants.…”
contrasting
confidence: 66%
“…CoNS coagulase-negative staphylococci occurred in 18.5% of infections leading to prosthetic valve dysfunction. In particular, the presence of Streptococcus gallolyticus etiology was correlated with ischemic embolic stroke and with the development of large vegetations [ 98 ].…”
Section: Microbiologymentioning
confidence: 99%
“…This multicentric study managed to provide a comprehensive analysis of infective endocarditis cases from western Romania during a four-year period and described in detail the antibiotic and antifungal management of the affected patients, along with the treatment complications and risk factors for mortality. Set in the global context of infective endocarditis, the data from Romania are limited to clinical monocentric studies [ 32 , 33 ], while country-wide epidemiologic data and real-world statistics are scarcely reported or lacking. Therefore, a real estimate of the recent evolution of cases over time is a difficult estimate in the country.…”
Section: Discussionmentioning
confidence: 99%
“…However, during the four-year period of the data analysis, nearly two-thirds (62.6%) of the participants in our research were older than 65. In older patients, the incidence of endocarditis was described to be about nine times greater compared to that in younger patients, although the threshold for old age is a matter of constant change and debate [ 32 , 33 , 34 ]. The age distribution of endocarditis is also changing, as endocarditis mostly impacted young individuals with rheumatic valvular disease, but it now primarily affects elderly patients, as rheumatic heart disease is widely prevented through prophylaxis methods [ 35 ].…”
Section: Discussionmentioning
confidence: 99%